2023
DOI: 10.3389/fenvs.2022.1080277
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and influencing factors of farmers’ sustainable livelihood response to ecocultural tourism in minority areas of China

Abstract: Ecocultural tourism plays an crucial role in promoting poverty reduction and farmers’ sustainable livelihood enhancement worldwide, which has attracted strong attention from scholars and society. However, the impact of ecological and cultural capital of farmers’ sustainable livelihoods have not been yet fully investigated. This paper modifies the sustainable livelihoods framework (SLF) and emphasizes the effects of ecological and cultural capital on farmers’ sustainable livelihoods. The modified SLF can be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…This framework offers a systematic approach for human societies to recognize and utilize natural resources. However, the SES framework overlooks the significant role of cultural factors within rural social-ecological systems, particularly those in tourism-oriented rural and ethnic areas (Wu et al 2022).…”
Section: Theoretical Basismentioning
confidence: 99%
See 3 more Smart Citations
“…This framework offers a systematic approach for human societies to recognize and utilize natural resources. However, the SES framework overlooks the significant role of cultural factors within rural social-ecological systems, particularly those in tourism-oriented rural and ethnic areas (Wu et al 2022).…”
Section: Theoretical Basismentioning
confidence: 99%
“…Second, rural tourism provides diversified livelihood opportunities, and farmers transform their livelihoods by proactively adapting to tourism disruptions. Finally, tourism development influences rural cultural and changes farmers' livelihoods, which contributes to the formation of new governance systems (Wu et al 2022, Xiao et al 2023. As a result, tourism development significantly impacts both the rural community level and the farmer level, and contributes to the dynamic evolution of ecological resilience in tourism villages.…”
Section: Theoretical Basismentioning
confidence: 99%
See 2 more Smart Citations
“…According to Zhou Li and Li Hongmei, human capital investment has provided important support for the relocation of farmers, enabling them to change from a traditional agricultural business model to a more flexible non-agricultural business model, therefore, it is necessary to strengthen the relevant education and training, improve the quality of the population, achieve effective use of resources, better development of local industries (Zhou et al, 2021). Jilin Wu and others found that farmers' sustainable livelihoods respond strongly to eco-cultural capital factors, and put forward livelihood transformation, strategic choice and improvement strategies and suggestions (Wu et al, 2023). In addition, latestage support is a special policy to improve the livelihood of migrants, and the key to guarantee the rights of migrants is to adjust the policy appropriately (Zhao et al, 2019).…”
Section: Social Adaptability (S)mentioning
confidence: 99%